2019
DOI: 10.1111/aos.14066
|View full text |Cite
|
Sign up to set email alerts
|

Macular vascular circulation and retinal oxygen saturation changes for idiopathic macular epiretinal membrane after vitrectomy

Abstract: Purpose: To investigate the postoperative changes in retinal-choroidal blood flow area and retinal vascular oxygen saturation among patients with idiopathic macular epiretinal membranes (iERMs).Methods: This study prospectively included 24 eyes of 24 consecutive patients who underwent vitrectomy for iERMs. The flow area of choriocapillary layer, retinal superficial capillary plexuses (SCPs) and retinal deep capillary plexuses (DCPs) were performed using optical coherence tomography angiography with angiovue pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
5
14
1
Order By: Relevance
“…It was observed that the CT and the blood flow area of choriocapillaris were reduced in patients with iERM. After vitrectomy, the blood flow area of choriocapillaris increased, while CT showed inconsistent results over previous studies [8-11].…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…It was observed that the CT and the blood flow area of choriocapillaris were reduced in patients with iERM. After vitrectomy, the blood flow area of choriocapillaris increased, while CT showed inconsistent results over previous studies [8-11].…”
Section: Introductioncontrasting
confidence: 62%
“…The iERM applies traction on the retina that causes an increase of CT and affects retinal vessels. Retinal arteries become dilated and tortuous in the natural course of ERM formation and as a result may alter the hemodynamics of the affected area [5-8, 18-22]. The blood flow area of choriocapillaris was reduced in patients with iERM and increased after vitrectomy [8, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our investigation, both these plexi have a peculiar progression: from baseline to the first month, we can see a reduction in vessel and perfusion density and, postoperatively, a significant increase. Li et al [14] have explained the variations found as retinal blood flow improvement after vitrectomy, followed by retinal arteriolar saturation which increases due to the removal of vitreous body, which could reduce the retinal oxygen consumption and allow oxygen diffusion and transport from the anterior segment. ere was no parallel change in venous saturation which suggests that it was possibly caused by better oxygen use during tissue repairment during this period.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the flow area of the SCP and CCP in ERM eyes had a statistically significant decrease, while that of the DCP had a marginally significant decrease compared with normal fellow eyes. It is generally believed that ERM distributed in the macula can exert a mechanical force on the superficial retinal vessels, primarily affecting the SCP vessels, and may cause proportionate impairment in the DCP and CCP [21][22][23]. However, we demonstrated that the flow area of the CCP, which theoretically suffered the least tractional force by ERM, was significantly reduced, while the flow area of the DCP was less affected.…”
Section: Discussionmentioning
confidence: 48%